Self-Evaluation Strategies in College Women Trying to Lose Weight: The Relative Use of Objective and Social Comparison Information - Wayment, Heidi A.; Eiler, Brian A.; Cavolo, Keragan (Frontiers in Psychology, 2020)
We examined patterns of self-evaluative information use in a sample of college women who were trying to lose weight (N = 306). Participants described their weight loss experiences and answered questions about their self-evaluative activity via an online survey. The analysis strategy examined the relative use of four types of self-evaluative information (objective, upward social comparison, lateral social comparison, downward social comparison) to meet three basic self-evaluative motives (accurate self-assessment, self-enhancement, self-improvement). We also examined the role that dissatisfaction, uncertainty, importance, and self-esteem played in the relative use of information and the relationship of these factors on weight loss success. Our findings support previous research showing the primacy of accurate and self-improvement motives in the domain of weight loss and the usefulness of lateral social comparison information for meeting all three motives. Women evaluating their weight reported using upward social comparison information most often, followed by objective information. Lateral and upward social comparison information were rated as more useful than downward social comparison information for meeting accuracy and self-improvement motives. Both lateral and downward social comparison information were reported as especially useful for self-enhancement, with upward social comparison information rated as least useful. Our study utilized an integrative approach for understanding self-evaluative processes in the area of college women’s weight loss. We found general support for our hypotheses regarding well-documented patterns of social comparison information usefulness for meeting three self-evaluative motives. Our data also support earlier research arguing that it is important to view information use in the context of multiple self-evaluative motives.